Letter from Julia Morgan to Cousin Lucy and Cousin Pierre Le Brun, December 25, 1898 - Julia Morgan::::::author::: (1898)
On December 25th, 1898 Julia Morgan writes to her cousins Lucy and Pierre Le Burn. She sends them Christmas wishes and notes that see has been busy. She explains that her and Avery gathered their friends for a last minute Christmas lunch. She updates them on Avery explaining that he is homesick but his French is progressing and that their new house is very nice. She closes the letter wishing them a happy New Year.